Paediatric oral sensorimotor interventions for chewing dysfunction: A scoping review. Issue 6 (22nd August 2021) - Wilson, Erin; Simione, Meg; Polley, Lydia
Abstract: Background: Chewing dysfunction can have adverse effects on growth, development and quality of life. There is a lack of evidence‐based consensus guidelines for sensorimotor intervention. To address this, we need to understand the current state of the science in clinical sensorimotor interventions for paediatric chewing dysfunction and systematically plan a research agenda and priorities for the field. Aims: The purpose of this scoping review was to examine the extent, range and nature of evidence for oral sensorimotor interventions for paediatric chewing dysfunction. Methods & Procedures: This scoping review entailed five phases that included: identification of the research question; identification of relevant studies; study selection; data charting; and collation, summarization and report of the results. Treatment studies that were peer‐reviewed and written in English were included. All studies involved a paediatric population and included an oral sensorimotor and/or chewing intervention. Information regarding study design, population, intervention, comparator, outcome measures and findings were extracted. Main Contribution: Of the 21 studies included in this scoping review, 53% were specific to children with cerebral palsy. All interventions were multi‐component in nature and the treatment studies included a range of study designs, but few were controlled trials with comparators. A wide variety of outcomes measures were used within and across studies to determine treatment effectiveness. Conclusions & Implications: The findings suggest that in a small number of studies, sensorimotor interventions provide preliminary evidence for effectiveness in specific populations. These and other treatment protocols must be trialled in additional clinical populations and settings to improve the evidence base for sensorimotor treatment of paediatric chewing dysfunction. This review also serves to help prioritize research agendas and further motivates the need for consensus‐based clinical guidelines for paediatric chewing treatment. What this paper adds: What is already known on the subject: Paediatric feeding disorders are highly prevalent and children often have chewing dysfunction that results in significant negative consequences. We lack evidence‐based sensorimotor treatment approaches for chewing dysfunction, which directly impacts the care clinicians can provide children. What this study adds to existing knowledge: This scoping review is the first step in examining the literature to understand the current state of the science for oral sensorimotor interventions for paediatric chewing dysfunction. Few randomized controlled studies were identified and a majority included children with cerebral palsy. Most of the interventions were multi‐component and included a variety of treatment approaches. What are the potential or actual clinical implications of this work?: The results of this scoping review can be used as an initial reference for clinicians selecting treatment approaches for chewing dysfunction. It also serves to help prioritize research agendas and further motivates the need for consensus‐based clinical guidelines for paediatric chewing treatment.